Konferencija „Šiuolaikinės architektūros raidos tendencijos“ (2009 m.) - Lupeikis, Kęstutis (Journal of Architecture and Urbanism, 2009)
Conference “Tendencies of contemporary Architecture” (2009). Journal of Architecture and Urbanism, 33(Supplement 1), pp. 249-250. First published online: 22 May 2013